2015
DOI: 10.1080/14786419.2014.996753
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ultrasound-assisted water extraction and β-cyclodextrin encapsulation of polyphenols fromMangifera indicastem bark in counteracting TNFα-induced endothelial dysfunction

Abstract: This study proposes an alternative technique to prevent heat degradation induced by classic procedures of bioactive compound extraction, comparing classical maceration/decoction in hot water of polyphenols from Mango (Mangifera indica L.) (MI) with ultrasound-assisted extraction (UAE) in a water solution of β-cyclodextrin (β-CD) at room temperature and testing their biological activity on TNFα-induced endothelial dysfunction. Both extracts counteracted TNFα effects on EAhy926 cells, down-modulating interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Moreover, a recent intervention study in humans reported moderate beneficial effects of the same mango fruit powder on microcirculation and endothelial function [18], mediated, at least partly, by the activation of endothelial nitric oxide synthase [18]. Similar results from studies with rats [15] and human umbilical vein cells [20] also suggest that polyphenols of aqueous extracts of Mango may protect endothelial cells. These results are of interest considering that impaired microvascular function is observed early in the development of type 2 diabetes mellitus and cardiovascular disease [21].…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, a recent intervention study in humans reported moderate beneficial effects of the same mango fruit powder on microcirculation and endothelial function [18], mediated, at least partly, by the activation of endothelial nitric oxide synthase [18]. Similar results from studies with rats [15] and human umbilical vein cells [20] also suggest that polyphenols of aqueous extracts of Mango may protect endothelial cells. These results are of interest considering that impaired microvascular function is observed early in the development of type 2 diabetes mellitus and cardiovascular disease [21].…”
Section: Introductionsupporting
confidence: 68%
“…Exposure to the extracts from Brassica oleracea significantly reduced the TNF-α induced expression of E-selectin, ICAM-1 and VCAM-1 (Kuntz and Kunz, 2014). Another study demonstrated the capacity of extracts from Mango (Mangifera indica L.) to counteract TNF-α effects on HUVECs, through the inhibition of IL-6, IL-8, COX-2 and ICAM-1, while restoring the expression of eNOS usually down-regulated by TNF-α (Mura et al, 2015). Interestingly, in an animal model, for example, supplementation of standard chow with cacao phenolic compounds in apolipoprotein E-deficient mice, lead to an anti-inflammatory effect justified by a reduction of VCAM-1 and ICAM-1 expressions, a decrease of oxidative stress markers and a reduction of cholesterol accumulation in plaque compared to control (Natsume and Baba, 2014).…”
Section: Cellular Effectsmentioning
confidence: 98%
“…The efficiency of extraction can be enhanced using this technique which may cause disruption of plant cell walls and improved mass transfer through the formation of cavitation babble effects (Entezari, 2004). The disadvantages of this method include poor purity, low efficiency, and lengthy process (Lu et al, 2012;Mura et al, 2015). Antimicrobial, antioxidant, antiinflammatory and anxiolytic activity (Arafat et al, 2020;Mahmud et al, 2009)…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%